Effect of irradiation on the atomic structure of borosilicate glasses. Issue 12 (21st July 2021) - Kumar, Rajesh; Jan, Amreen; Bauchy, Mathieu; Krishnan, N. M. Anoop
Abstract: Borosilicate glasses incorporating high‐level nuclear waste are exposed to high‐energy radiations during their storage in the deep geological repositories. However, the effect of radiation on the atomic structure of borosilicate glasses remains poorly understood. Herein, using molecular dynamics simulations, we study the irradiation‐induced structural changes of a series of calcium‐sodium borosilicate glasses with varying Si/B molar ratios—ranging from pure silicate to pure borate glasses. We observe that irradiation leads to an increase in disorder, both in the short‐ and medium‐range, as evidenced by the enthalpy, coordination number, and ring distribution. In particular, the impact of the change in the atomic structure (due to radiation) on the glass volume is investigated. Interestingly, we observe a composition‐dependent transition in the volumetric response of borosilicate glasses under irradiation—wherein borate‐rich compositions tend to swell, whereas silica‐rich glasses tend to densify. Through a detailed analysis of the structure, we demonstrate two competing mechanisms contributing to the volume change, i.e., a decrease in the coordination number of boron atoms and a reduction in the average silicon inter‐polytope angle. We also show that the increase in the disorder in the medium‐range order may play a major role in governing the volumetric changes in the irradiated structure in a non‐trivial fashion. Altogether, the present study highlights that irradiation has a non‐trivial effect on borosilicate glasses, which, in turn, could impact their corrosion kinetics.